Measuring Non-Linear Absolute Mobility in Distribution of Income in Iran - Hossein Raghfar; Mir Hossein Mousavi; Batoul Azari Beni (پژوهشهای اقتصادی, 2016)
In most countries, there is no panel data for different households over time. However, cross-sectional data are usually available. Using a cross-sectional dataset, a given group of households cannot be examined for subsequent years. To solve this problem, we used data from the pseudo-panels. The pseudo-panel approach provides cohort generations of households over time. This method enables us to track the performance of each cohort over time. Here, we study the absolute mobility in Iran with 23 periods and 20 generations. Income mobility is an index which indicates the degree of inequality of opportunities in a society. It is measured as either conditional or absolute one. In conditional mobility, fixed effects are considered, however in absolute mobility it is not so.The fixed effects indicate heterogeneity among individuals. Our results indicate that the absolute income mobility is low and Inequality of opportunity is decreasing over time. But the speed of decrease in inequality is low.